Modern Genetic Education: How Does It Meet Students’ Requests? - T. A. Sedykh; L. A. Amirova; L. A. Gaysina; G. F. Galikeeva; A. I. Fazlutdinova; N. V. Sukhanova (Высшее образование в России)
The role of genetics in modern society is growing, which makes new demands on the quality of training specialists in this field. The article considers the results of the student survey carried out at universities universities of the Republic of Bashkortostan in November 2021 (N=209). The aim of the survey was an analysis of the correspondence of the quality of genetic education to the needs of students. It was found that despite the satisfaction of the majority of the surveyed students with the quality of genetic education, there are problems in understanding modern sections of genetics, such as molecular genetics, toxicological genetics, genomics. The students are not sufficiently involved in scientific research, most of them prefer the traditional forms of teaching and learning, only few of them are aware of modern online resources and MOOCs. The part of students is interested in the development of practical skills in the field of genetic research. The data obtained lead to the conclusion that it is necessary to revise the existing methods of teaching genetics in universities and search for new effective approaches to improve the quality of mastering genetic disciplines.